Limited Reliability of Computed Tomographic Perfusion Acute Infarct Volume Measurements Compared With Diffusion-Weighted Imaging in Anterior Circulation Stroke. Issue 2 (February 2015) - Schaefer, Pamela W.; Souza, Leticia; Kamalian, Shervin; Hirsch, Joshua A.; Yoo, Albert J.; Kamalian, Shahmir; Gonzalez, R. Gilberto; Lev, Michael H.
Abstract : Background and Purpose—: Diffusion-weighted imaging (DWI) can reliably identify critically ischemic tissue shortly after stroke onset. We tested whether thresholded computed tomographic cerebral blood flow (CT-CBF) and CT-cerebral blood volume (CT-CBV) maps are sufficiently accurate to substitute for DWI for estimating the critically ischemic tissue volume. Methods—: Ischemic volumes of 55 patients with acute anterior circulation stroke were assessed on DWI by visual segmentation and on CT-CBF and CT-CBV with segmentation using 15% and 30% thresholds, respectively. The contrast:noise ratios of ischemic regions on the DWI and CT perfusion (CTP) images were measured. Correlation and Bland–Altman analyses were used to assess the reliability of CTP. Results—: Mean contrast:noise ratios for DWI, CT-CBF, and CT-CBV were 4.3, 0.9, and 0.4, respectively. CTP and DWI lesion volumes were highly correlated ( R 2 =0.87 for CT-CBF; R 2 =0.83 for CT-CBV; P <0.001). Bland–Altman analyses revealed little systemic bias (−2.6 mL) but high measurement variability (95% confidence interval, ±56.7 mL) between mean CT-CBF and DWI lesion volumes, and systemic bias (−26 mL) and high measurement variability (95% confidence interval, ±64.0 mL) between mean CT-CBV and DWI lesion volumes. A simulated treatment study demonstrated that using CTP-CBF instead of DWI for detecting a statistically significant effect would require at least twice as many patients. Conclusions—: The poor contrast:noise ratios of CT-CBV and CT-CBF compared with those of DWI result in large measurement error, making it problematic to substitute CTP for DWI in selecting individual acute stroke patients for treatment. CTP could be used for treatment studies of patient groups, but the number of patients needed to identify a significant effect is much higher than the number needed if DWI is used.